A Blockchain-based Halal Certificate Recording and Verification Prototype - Anak Agung Gde Agung; Heru Nugroho; Robbi Hendriyanto (Society of Visual Informatics, 2022)
Halal certification assures that a product or a service has been created, processed, and delivered according to Islamic laws. Currently, the certificate is printed on a security paper and includes a QR code that can be used to verify the certificate online. However, there are some problems with the ongoing certificate verification process. The verification site is centralized, creating a single point of failure. The current verification system is also unable to detect the modified printed certificate. The research aims to propose an alternative halal certificate recording and verification system. A smart contract that runs on the Ethereum blockchain is developed and deployed for that purpose. As a result, the average certificate creation cost is US20.035, and the process requires 5.75 seconds, while verification is free, and the result can be obtained in about one second. Utilizing the blockchain to store and verify the halal certificate increases trust in the product or service since once the data is stored, it cannot be changed and accessible to the public. Nodes around the world replicate the blockchain to ensure service availability. For future consideration, the system can be extended to automate and track the halal application process and integrated as an alternative to the current system by implementing multiple signatures in the smart contract for each party. Furthermore, the system can be integrated with a peer-to-peer sharing system such as IPFS to store the digital certificate